Effects of mir-195 Targeted Regulation of JAK2 on Proliferation, Invasion, and Apoptosis of Gastric Cancer Cells. (26th July 2022) - Zhang, Yu; Zhuang, Kun; Yuan, Shanshan; Si, Wangli; Li, Yijun; Zhang, Jun; Liu, Jiaming
Abstract : Background . Overexpression of miR-195 can make gastric cancer cells stay in G1/G2 phase. miR-195 has been shown to inhibit gastric cancer cell replication and accelerate cell death by targeting JAK2. However, the relationship between miR-195, JAK2, and gastric cancer is not clear. Objective . To observe the effect of mir-195 regulated by JAK2 on the growth, invasion, and death of gastric cancer cells. Methods . MGC803 and NCI gastric N87 cells were introduced into the negative control sequences of miR-195 and RNA, respectively. To detect the expression of miR-195 in cells, to detect the effect of miR-195 on mitosis and proliferation of tumor cells, to analyze the effect of miR-195 on cell invasion and metastasis, and to detect the regulation of miR-195 on JAK2 expression. Results . The level of miR-195 in miR-195-MIMICS group was significantly higher than that in miR-NC group. The cell survival rate of miR-195 mimic group was lower than that of miR-NC group (P < 0.05 ). Compared with miR-NC group, the number of cells in G1 phase increased, the cells in G2 phase and S phase decreased, and the proportion of cells in G2 and S phase decreased in miR-195 mimic group. The scratch distance of miR-195 simulator group was larger than that of control group. The number of invasive cells in the miR-195 mimic group was significantly lower than that in the control group. The expression of JAK2 protein in miR-195 mimic group was lower than that in miR-NC group. There was a significant negative correlation between the expression level of miR-195 and JAK2 (rhabdomile 0.326 and record 0.00). There are continuous interaction fragments between JAK2 and miR-195. The luciferase activity of miR-195 mimic and wild type JAK2 sequence expression vector was significantly lower than that of wild type JAK2 sequence expression vector. Conclusion . miR-195 may inhibit the occurrence, metastasis, and invasion of gastric tumor by downregulating the expression of JAK2. miR-195/JAK2 may be a new molecular target for the treatment of gastrointestinal tumors.